The clinical association between coagulation indexes, platelet-related parameters, and bone metastasis of newly diagnosed prostate cancer - Zhiwei Yu; Mingxue Yuan; Guojun Chen (European Journal of Medical Research, 2023)
Abstract Background At present, much evidence shows that many cancers have a high risk of thrombosis. Several studies have shown the prognostic value of platelet-related parameters and coagulation indexes in prostate cancer (PCa). However, the association between platelet-related parameters, coagulation indexes and bone metastasis of Pca is unclear. Methods A total of 234 pathologically diagnosed patients with Pca were consecutively collected and stratified into the bone metastasis group and non-bone metastasis group according to the results of the bone scan. ROC curve analysis was used to explore the auxiliary predictive value of single and combined parameters for bone metastasis in Pca patients. Univariate and multivariate Logistic regression analyses were used to determine the relationship between platelet-related parameters, coagulation indexes, and bone metastasis of Pca. Results Platelet count (PLT), fibrinogen (Fib), prostate-specific antigen (PSA), and D-dimer (DD) levels of the bone metastasis group were significantly higher than the non-bone metastasis group (P = 0.010, P < 0.001, P < 0.001, and P < 0.001, respectively). This study confirmed that PLT, PSA, DD and Fib have auxiliary predictive value for prostate cancer bone metastasis. After the combination of PLT, PSA, DD and Fib, the area under the curve, sensitivity and specificity increased significantly. The univariate logistic analysis demonstrated that PLT (OR: 1.008, P = 0.011), DD (OR: 2.690, P < 0.001), PSA (OR: 1.073, P < 0.001), Gleason score (OR: 7.060, P < 0.001), and Fib (OR: 2.082, P < 0.001) were significantly positively correlated with bone metastasis of Pca. Multivariate analysis showed that PSA (OR: 1.075, P < 0.001), DD (OR: 2.152, P < 0.001), Gleason score (OR: 2.904, P < 0.001), and Fib (OR: 1.706, P < 0.001) were independent risk factors for bone metastasis of Pca after adjusting for Age, BMI and other confounding factors. Conclusions Higher platelet, D-dimer, prostate-specific antigen, Gleason score, and fibrinogen levels may predict a worse prognosis in patients with Pca. PLT, DD, and Fib, as readily available and relatively inexpensive indicators, help predict bone metastasis of Pca. It is suggested that PLT, DD and Fib may be helpful in the risk stratification of Pca.